Refraction of 1-year-old children after atropine cycloplegia. - Ingram, R M (1979)
The refractions of 1648 children aged 11 to 13 months are reported. Atropine 1% was used for cycloplegia. 11.83% of the children had bilateral hypermetropia of +2.00 or more D. 13.23% of them had +1.50 or more D astigmatism in one or both eyes, and 6.5% had anisometropia. Anisometropia was significantly (P=0.000 001%) associated with bilateral hypermetropia, but even more significantly (P=0.000 000 4%) associated with astigmatism of +1.50 or more D in one or both eyes.